1990
DOI: 10.1128/mcb.10.10.5586
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA unwinding and modifying activity is detected ubiquitously in primary tissues and cell lines.

Abstract: A double-stranded RNA unwinding and modifying activity was found to be present in a wide range of tissues and cell types. The level of activity did not vary significantly with respect to the state of cell differentiation, cell cycle, or transformation. Thus, the unwinding and modifying activity, localized in the nucleus in somatic cells and capable of converting many adenosine residues to inosine, appears to be one of the housekeeping genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 24 publications
(26 reference statements)
5
56
0
Order By: Relevance
“…Even though this probe contained the sequence for the first dsRNA binding domain, it did not cross-hybridize with other mRNAs encoding dsRNA binding domains. The mRNA for the dsRNA adenosine deaminase was present in all tissues examined, in agreement with earlier reports that demonstrated a widespread expression of the deaminase (45). Northern blot analysis of poly(A) ϩ RNA from calf thymus with the partial bovine cDNA clone as a probe also showed a band of Ͼ7.5 kb (data not shown).…”
Section: Northern Blot Analysis Northern Blot Analysis Of Human Tisssupporting
confidence: 77%
“…Even though this probe contained the sequence for the first dsRNA binding domain, it did not cross-hybridize with other mRNAs encoding dsRNA binding domains. The mRNA for the dsRNA adenosine deaminase was present in all tissues examined, in agreement with earlier reports that demonstrated a widespread expression of the deaminase (45). Northern blot analysis of poly(A) ϩ RNA from calf thymus with the partial bovine cDNA clone as a probe also showed a band of Ͼ7.5 kb (data not shown).…”
Section: Northern Blot Analysis Northern Blot Analysis Of Human Tisssupporting
confidence: 77%
“…Further experiments revealed that dsRAD was present in post-MBT embryos but was localized to the nucleus and thus not detected in early experiments involving cytoplasmic microinjections (5). dsRAD has also been shown to be nuclear in the somatic cells of mammals (34). Taken together, these results raised the possibility that dsRAD is in the nuclei of stage VI oocytes and exists in the cytoplasm of eggs and early embryos because it is released from the nucleus during meiotic maturation, the process by which a stage VI oocyte becomes an egg (for a review, see reference 31).…”
mentioning
confidence: 99%
“…Although the level of ADAR1 transcript is increased by treatment with both IFN-␣ and IFN-␥ (9, 13, 17), a significant basal level of ADAR1 transcript is observed in human cell lines and organs in the absence of IFN treatment (9)(10)(11). Because of the important role that ADAR1 plays in the editing of cellular neurotransmitter receptor pre-mRNAs in the apparent absence of IFN treatment (2,18) coupled with the unresolved origin of the constitutively expressed Ϸ110-kDa form of ADAR1 protein ubiquitously observed at high levels in the nucleus of animal cells in the absence of IFN treatment (9,20), and because of the potential role of the IFN-inducible Ϸ150-kDa form of ADAR1 in the antiviral actions of IFN (9, 21), we have attempted to define the elements responsible for ADAR1 transcriptional control. As a step toward this goal, we isolated and characterized genomic clones of the human ADAR1 gene (14,15).…”
mentioning
confidence: 99%